Investigation on Natural Convection in a Square Porous Cavity with an Open Side (Journal of Engineering, 2024)
Natural convection in a porous, rectangular hollow full of saturated air was investigated numerically in the current study. The bottom side was warmed with a continuous heat flux, the right side's temperature was kept at (Tc), the left wall was opened to the surroundings, and the top side was insulated. The pertinent filled-out research parameters in the current experiment were four heat flux values (1500, 3000, 4500, and 6000 W/m²) and three Darcy’s numbers (Da1=4.025×10-10, Da2=4.025×10-8, Da3=4.025×10-6). COMSOL Multiphysics 5.5a, using finite elements and a relying Brinkman-Darcy extended model, was employed to resolve government equations. Local thermal balance simulation was assumed in this solution. Energy transfer and momentum were studied using isotherms and streamlines. The findings appeared that the flow velocity improved with the rising Darcy number, especially in the case of Da3, as well as increasing the average Nusselt number about 110 % and 45% for Da3 and Da2 compared with Da1. Additionally, the increase in heat flux will increase the heat transfer, especially with Da3.